2019
DOI: 10.3390/ijms20061335
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Porcine Endometrium during Implantation after In Vitro Stimulation by Adiponectin

Abstract: Comprehensive understanding of the regulatory mechanism of the implantation process in pigs is crucial for reproductive success. The endometrium plays an important role in regulating the establishment and maintenance of gestation. The goal of the current study was to determine the effect of adiponectin on the global expression pattern of genes and relationships among differentially expressed genes (DE-genes) in the porcine endometrium during implantation using microarrays. Diverse transcriptome analyses includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 68 publications
0
9
0
1
Order By: Relevance
“…Smolinska et al report a research article describing a comparative transcriptomic study performed in control and adiponectin-treated endometrial tissues isolated from 15- to 16-day-pregnant pigs. The findings evidence that adiponectin affects processes important for reproductive success, such as cell proliferation, cell adhesion, and synthesis of steroids, prostaglandins, and cytokines [11]. The anti-atherogenic role of adiponectin has been widely recognized.…”
mentioning
confidence: 99%
“…Smolinska et al report a research article describing a comparative transcriptomic study performed in control and adiponectin-treated endometrial tissues isolated from 15- to 16-day-pregnant pigs. The findings evidence that adiponectin affects processes important for reproductive success, such as cell proliferation, cell adhesion, and synthesis of steroids, prostaglandins, and cytokines [11]. The anti-atherogenic role of adiponectin has been widely recognized.…”
mentioning
confidence: 99%
“…Moreover, adiponectin significantly stimulated proliferation and suppressed apoptosis of porcine uterine luminal epithelial cells and would enhance uterine receptivity for embryo implantation. Study of Smolinska et al 2019 [63] confirmed, that adiponectin-stimulated proliferation is related to activation of the PI3 K.…”
Section: Genes Related To Signaling and Metabolismmentioning
confidence: 90%
“…Our previous research also demonstrated that adiponectin modulates the expression of genes encoding the secretion of the key steroidogenic enzymes and steroid hormones during early pregnancy. The obtained data suggest that adiponectin may influence the expression of genes that are directly or indirectly implicated in the regulation of uterine function during early gestation (Smolinska et al., 2016; Smolinska et al, 2019). The modulatory effect of OXB on the expression of ADIPOQ could point to the concurrent activity of both hormones in the regulation of maternal metabolism, apoptotic processes and immune system activity during the implantation period.…”
Section: Discussionmentioning
confidence: 99%